INVESTIGATING THE IMPACT OF E-LEARNING ASSESSMENT USING PORTFOLIO ON WRITING ENGAGEMENT: INDONESIAN ISLAMIC EFL HIGH SCHOOL STUDENTS’ PERCEPTION - Annisa Diah Nur Alamsyah; Dedeh Rohayati (Universitas Galuh, 2022)
This paper reports an analysis of students’ perception on the impact e-learning assessment using portfolios on writing engagement. This research employed a case study approach. Questionnaires were used as data collection instruments. The participant of this study was students of Islamic High School of grade 10 in Garut and the data collection was obtained from the questionnaire with EFL Students. The results showed that the use of e-learning assessment through portfolio was very influential on students in collecting assignments. The results also show that the student's perception of e-learning assessment through the portfolio is very influential on students ' writing engagement.